The Effect of Parenting and Learning Discipline on Students' Mathematics Achievement - Kusumayanti, Andi; Suci, Suci Risdayanti (Alauddin Journal of Mathematics Education, 2024)
This study aims to: (1) describe parental education, (2) learning discipline, (3) students' mathematics learning outcomes, and examine the effect of (4) parental education, (5) learning discipline, and (6) both simultaneously on students' mathematics learning outcomes in Class X SMA Negeri 5 Bulukumba. This research uses a comparative causal method (ex post facto) with a quantitative approach. The sample consisted of 105 grade X students, with instruments in the form of questionnaires on parenting patterns and learning discipline. The data were analysed using descriptive and inferential statistics through simple and multiple linear regression. The results showed that: (1) democratic parenting is dominant in the good category (mean score 54.43); (2) learning discipline is in the high category (mean score 53.40); (3) students' mathematics learning outcomes are also in the high category (mean score 62.17); (4) democratic parenting and (5) learning discipline have a positive effect on mathematics learning outcomes; and (6) both simultaneously have a significant effect on students' mathematics learning outcomes.